The Nature of Processes Affecting the Solubility, Viscosity, and Density Characteristics of Aqueous Electrolyte Systems - Kambarova, Galiya; Nazarbek, Ulzhalgas; Nazarbekova, Saule; Abdurazova, Perizat; Raiymbekov, Yerkebulan (Pandawa Institute, 2025)
This study investigates the key factors influencing the solubility, viscosity, and density of aqueous electrolyte systems. Model solutions of types 1-1, 1-2, 2-1, and 2-2 electrolytes were examined across a wide concentration range. The results show that solubility increases with temperature due to a higher proportion of free water molecules, while greater electrolyte concentrations lead to a rise in viscosity and density. It was found that ion radius and charge density strongly impact solution properties: larger ion radii and lower charge densities decrease viscosity and increase density, whereas smaller radii and higher charge densities have the opposite effect. The findings offer new insights into the relationship between ionic parameters and macroscopic solution behavior, supported by mathematical modeling and graphical analysis.